Low-intensity transcranial ultrasound stimulation facilitates hand motor function and cortical excitability: A crossover, randomized, double blind study - Zhang, Meng-Fei; Chen, Wei-Zhou; Huang, Fub-Biao; Peng, Zhi-Yong; Quan, Ying-Chan; Tang, Zhi-Ming (Frontiers in Neurology, 2022)
Objective Transcranial ultrasound stimulation (TUS) is a new form of non-invasive brain stimulation. Low-intensity TUS is considered highly safe. We aimed to investigate the effect of low-intensity TUS on hand reaction responses and cortical excitability in healthy adults. Methods This study used a crossover, randomized, and double-blind design. A total of 20 healthy participants were recruited for the study. All the participants received TUS and sham stimulation on separate days in random order. The finger tapping test (tapping score by using a tablet) and motor evoked potential (MEP) were assessed before and after stimulation, and discomfort levels were assessed using a visual analog scale (VAS) score. Results No significant differences in tapping score or MEP amplitude between the two experimental conditions were registered before stimulation. After stimulation, tapping scores were increased regardless of the specific treatment, and the real stimulation condition receiving TUS (90.4 ± 11.0 points) outperformed the sham stimulation condition (86.1 ± 8.4 points) (p = 0.002). The MEP latency of real TUS (21.85 ± 1.33 ms) was shorter than that of sham TUS (22.42 ± 1.43 ms) (p < 0.001). MEP amplitude of real TUS (132.18 ± 23.28 μV) was higher than that of sham TUS (114.74 ± 25.5 μV, p = 0.005). There was no significant difference in the discomfort score between the two conditions (p = 0.163). Conclusion Transcranial ultrasound stimulation (TUS) can decrease the hand reaction response time and latency of the MEP, enhance the excitability of the motor cortex, and improve hand motor function in healthy individuals without obvious discomfort.